Unusual renal and colonic mass - description of a rare case (Indian Journal of Case Reports, 2019)
Seminoma is a germ cell tumor arising from the testis and rarely from mediastinum or other extra-gonadal locations. Seminomas account for 40% of all GCTs. Seminoma can rarely metastasize to kidney and metastasis to the GI tract is least likely with an incidence of less than 1%. It is one of the most treatable and curable cancers, with a survival rate above 95% if discovered in early stages. We are presenting a rare case of metastatic seminoma in a 40-year-old male who presented with a renal and intestinal mass two years after orchidectomy for seminoma which was PLAP negative.